Demokrati og legitimitet - Rancière og kritikken af deliberativt demokrati - Holm, Andreas Beck (Slagmark - Tidsskrift for idéhistorie, 2018)
What constitutes the legitimacy of democratic rule? In this paper it is argued that the answer to this question is the repression of an original exercise of power, which cannot be legitimate, because its function is to delimit and define the demos. Every type of government is based on a similar moment of illegitimacy, and every type of government seeks to make this invisible by inventing a myth of origin – in the case of democracy, this myth is the demos as a pre-existing entity. The paper traces this myth, first in Rousseau’s concept of general will, then in Gutman and Thompson’s contemporary version of a democratic narrative as ‘deliberative democracy’. The common denominator is that these narratives work only as a function of a constitutive void, which both constitutes and disqualifies them. Finally, it is argued that Rancière presents us with an alternative, making it possible to formulate a concept of democracy that does not need a legitimizing myth.